ENGLISH SPECIFIC PURPOSES PERSPECTIVE: IDENTIFYING ENGLISH LANGUAGE NEEDS OF GUIDANCE AND COUNSELLING STUDENTS - Husain, Nurlaila; Ali, Sri Widyarti (International Journal of Research on English Teaching and Applied Linguistics, 2024)
The development of effective English language proficiency among Guidance and Counselling students is crucial for their academic success and future professional endeavours. However, there is a gap in the literature concerning the specific language needs and preferences of this student population within the field of English for Specific Purposes (ESP). This study aims to identify the essential English sub-skills required by Guidance and Counselling students currently enrolled in the second semester of the 2022â€“2023 academic year, encompassing listening, speaking, reading, and writing. Employing a descriptive quantitative method, data was collected through an online questionnaire administered to 53 students. The findings highlight the importance of listening comprehension skills, with 79.3% recognizing the value of understanding lectures and classmates during English lessons. Additionally, the study emphasizes the significance of proficient speaking abilities for facilitating dialogues, with 66.7% valuing discussions on general and current topics with classmates. Furthermore, the ability to critically analyse internet articles (64.4%) emerged as the most valued reading skill for evidence-based practice and cross-cultural sensitivity. Lastly, the participants most recognized the importance of writing skills for conducting group research in English (56.3%). Overall, the study underscores the multidimensional nature of English language proficiency required for Guidance and Counselling students and the need for an integrated approach to language education that fosters well-rounded competence. By addressing these language needs, educational institutions can better prepare students for the communicative demands of their future roles as counsellors.Â Â